2018
DOI: 10.1093/molbev/msy236
|View full text |Cite|
|
Sign up to set email alerts
|

Degenerative Expansion of a Young Supergene

Abstract: Long-term suppression of recombination ultimately leads to gene loss, as demonstrated by the depauperate Y and W chromosomes of long-established pairs of XY and ZW chromosomes. The young social supergene of the Solenopsis invicta red fire ant provides a powerful system to examine the effects of suppressed recombination over a shorter timescale. The two variants of this supergene are carried by a pair of heteromorphic chromosomes, referred to as the social B and social b (SB and Sb) chrom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 72 publications
(120 reference statements)
4
56
0
Order By: Relevance
“…In fire ants, several TEs are presumably active based on their germline expression and many TEs have substantial expanded in the Sb haplotype (Lee & Wang, ; Stolle et al, ; Wang et al, ). Our study identified ten TEs that were differentially expressed based on genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fire ants, several TEs are presumably active based on their germline expression and many TEs have substantial expanded in the Sb haplotype (Lee & Wang, ; Stolle et al, ; Wang et al, ). Our study identified ten TEs that were differentially expressed based on genotype.…”
Section: Discussionmentioning
confidence: 99%
“…In fire ants, several TEs are presumably active based on their germline expression and many TEs have substantial expanded in the Sb haplotype (Lee & Wang, 2018;Stolle et al, 2019;Wang et al, 2013).…”
Section: Antennal Gene Expression Differences Between the Three Wormentioning
confidence: 99%
“…Additionally, male ants are haploid and therefore a haplotype with a deleted gene would be fully exposed to selection in males. The resulting selection against deletion would be much higher than in diploid species which would still carry an unaffected gene copy (35,39).…”
Section: Introductionmentioning
confidence: 99%
“…Sb/Sb queens are rare in the wild and their offspring are unviable (32,33). Recombination is severely repressed between SB and Sb (31,34) due to the presence of at least 3 inversions (35,36). Similarly to a Y chromosome, Sb thus lacks recombination opportunities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation